Failure Evaluation of Ball Bearing for Prognostics. (2016) - Nistane, V.M.; Harsha, S.P.
Abstract: Vibration analysis is extensively used for ball bearing condition monitoring to monitor vibration signal. The measurement of vibration and their signal analysis plays a significant role for investigation of defect. Vibration signature divulges important information about development of defect within the system. Vibration signature of ball bearing for lifetime assessment in time domain analysis shows variation of features due to development of defects over the span of bearing. The trend extrapolation of features illustrates failure variation in the bearing. Every defect harvests characteristics vibration in the ball bearings. After examining vibration spectrum may provide valuable information about defects develop in the bearing. In this paper Bearing Prognostic Simulator (BPS) as test rig is used to examine vibration signature of bearing throughout the lifespan. The bearing failure evaluation is assessing to investigate variation of defect in bearing under radial load and constant speed. Acquired vibration signatures are scrutinized to extract statistical feature for proper representation of failure evaluation. When any irregularities are noticed in statistical measures, vibration spectra will provide enough information to express position of defect in the bearing.